Fine wine flavour perception and appreciation: Blending neuronal processes, tasting methods and expertise - Malfeito-Ferreira, Manuel (2021)
Background: Wine flavour has been methodically studied since the beginning of sensory research, with various purposes relating to product quality and consumer preferences. Recent advances in neuroscience have provided a deeper insight into how the perceptions elicited by flavour-active molecules are processed by the brain. In particular, the implications of the synthetic, emotional and mental imagery features of olfaction, together with the cross-modal influences on flavour perception, should be properly acknowledged in tasting methods. Scope and approach: The purpose of this review is to present a critical appraisal of current tasting methods, with focus on those that are most frequently applied to assess fine wine. The remarkable ability to distinguish odours, and the emotional nature of the sense of smell, are the basis for the development of alternative tasting approaches that have lead to recent advances. The limitations of aroma and flavour descriptive analysis resulting from the synthetic nature of olfaction will be discussed and, in particular, those limitations that relate to the holistic evaluation of quality that constitutes the core of aesthetic judgements. Key findings and conclusions: We argue that the conventional tasting sequence and the dominance given to descriptive analysis contributes to the subordination of the holistic nature of wine assessment. Further, expert quality judgements may be strongly biased by cognitive factors and wine preferences. Hence, the highest level of expertise may be attained when individuals are able to recognise a fine wine’s synthetic properties (e.g. complexity, harmony, persistence) in association with socio-cultural aspects (e.g. origin, winemaking traditions), and then produce aesthetic judgements independently from wine enjoyment. Overall, fine wines may be defined as those characterized by superior synthetic or holistic properties that are perceived and appreciated by individuals who understand, and in the context of, their cultural meaning